2000
DOI: 10.1677/joe.0.1670371
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localisation of vascular endothelial growth factor and basic fibroblast growth factor during the final growth of bovine ovarian follicles

Abstract: Locally produced growth factors may have important modulatory roles in final ovarian follicular growth. The aim of this study was to investigate the possible participation of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (FGF2) in bovine follicles during final growth. Ovaries were collected from a slaughterhouse within 10-20 min after exsanguination. A classification of follicles into five groups (<0·5; >0·5-5; >5-20; >20-180; >180 ng/ml) was performed according to the follicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
5
10

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(158 citation statements)
references
References 49 publications
9
134
5
10
Order By: Relevance
“…In contrast with the cow (Berisha et al 2000a), the FSHR mRNA expression trended to decrease during porcine follicle maturation. This agrees with findings by Cardenas & Pope (2002).…”
Section: Follicle Groupcontrasting
confidence: 58%
See 2 more Smart Citations
“…In contrast with the cow (Berisha et al 2000a), the FSHR mRNA expression trended to decrease during porcine follicle maturation. This agrees with findings by Cardenas & Pope (2002).…”
Section: Follicle Groupcontrasting
confidence: 58%
“…Zeleznik et al (1981) suggested that the selected follicles possess more elaborate microvasculature than other follicles. We concluded from studies in cow that vascular endothelial growth factor (VEGFA) and fibroblast growth factor 2 (FGF2) are involved in the proliferation of capillaries that accompany the selection of the preovulatory follicle resulting in an increased supply of nutrients, precursors and hormones, and therefore supporting the growth of the dominant follicle (Berisha et al 2000a, Yamashita et al 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in VEGF, an angiogenic factor, occurred in the follicles of cattle (Berisha et al 2000) and pigs (Barboni et al 2000) as diameter increased. The synthesis and secretion of VEGF increased in cultures of granulosa cells in cattle (Schams et al 2001) and monkeys (Martinez-Chequer et al 2003) when exposed to IGF-I.…”
Section: Vegf and Vascularitymentioning
confidence: 99%
“…Recently, it has been shown that vascular endothelial growth factor and FGF families are involved in the proliferation of capillaries that accompanies the selection of the preovulatory follicle. This results in an increased supply of nutrients and precursors, therefore supporting the growth of the dominant follicle in bovine ovaries (Berisha et al 2000a). In addition, FGF2 may play a significant role in bovine granulosa cell steroidogenesis (Vernon & Spicer 1994), anti-apoptotic action (Peluso et al 2001) and differentiation of granulosa cells (GCs) into luteal cells during the process of luteinisation (Lavranos et al 1994).…”
Section: Introductionmentioning
confidence: 99%